The course in advanced midwifery and neonatal care - E.M Maclure (AOSIS, 1981)
According to one dictionary the meaning of Advanced is: to be ahead of most others or at a far-on stage of education, thought, emancipation, life, etc. It has been said that teaching is a success only when it enables students to excel their teachers. How many teachers, clinical or academic, can accept this, albeit with a pang? However, by teaching the teachers, a nucleus of confident enthusiasts can be formed who will be, as it were, the RNA and DNA of the midwifery profession, at a far-on stage of education, thought, emancipation, life, etc.